First numbers - Davis, Caroline (Englaned Armadillo, Leicester, 2012)
This early learning book is the perfect way to introduce your child to their first numbers. Count 1 kite in the sky, 2 trees in the park, 3 aliens in space, 4 balloons at the party, and 5 mermaids under the sea
Arithmetic notion
Keywords: Books for Babies; Counting